Are we really studying resilience in sport? A critical review of adopted methodologies - Kegelaers, Jolan (Frontiers in Psychology, 2023)
Psychological resilience has gained considerable attention in sport. Nevertheless, the construct often remains poorly understood and multiple conceptual and methodological issues pervade the literature. The purpose of the present article is to provide a critical review of the commonly adopted methodologies to study resilience in sport. This review is divided into four sections. The first section will briefly discuss opposing conceptualizations of resilience as a static trait or a dynamic process. The second section will then discuss key methodological implications relating to the conceptualization of resilience as a dynamic process. In the third section, common methodologies to study resilience in sport are presented and critically reviewed. These methodologies are broadly divided into: (i) self-report resilience measures, (ii) qualitative research, and (iii) direct assessment of functioning in relation to observed adversity. In the final section, some avenues for future research are offered.